Guard And Security Team for Regional Development in Preventing Criminal Acts of Corruption - Hibnu Nugroho (Faculty of Law, Universitas Jenderal Soedirman, 2021)
To prevent the occurrence of criminal acts of corruption, the Attorney General's Office issued a Decree of the Attorney General of the Republic of Indonesia Number: KEP-152/A/JA/10/2015 dated October 1, 2015, followed by Instruction of the Attorney General of the Republic of Indonesia Number: INS-001/A/JA/10/2015 concerning the Establishment of the Government and Development Guard and Security Team (TP4) of the Republic of Indonesia Prosecutor's Office, to be followed up by all levels of the Attorney General's Office throughout Indonesia. At the regional level, the TP4D institution is expected to be able to prevent the emergence of potential corruption in projects in the regions by assisting from the inception of contracts. With assistance, the parties implementing contracts also feel the safety of being assisted by experts in the field of law, especially those related to corruption. This paper discussed the performance of the TP4D (Guard and Security Team for Government and Regional Development). This institution was dissolved after four years running and revoked based on Attorney General's Instruction Number 7 of 2019 concerning Implementation of Attorney General Decree Number 345 of 2019 concerning the Revocation of the TP4. The existence of the TP4D was actually perceived to provide many benefits by development implementers in the regions, especially its prevention of the emergence of maladministration and the potential for corruption. This article was part of the reseach of Professor Grant scheme of 2020.Keywords: prevention, corruption, escort, regional development